Perinephric and Ovarian Metastasis from Advanced Urothelial Carcinoma of the Bladder: A Rare Dismal Disease - A Case Report - Vias, Poorva; Saklani, Ashish; Singh, Suman; Thakur, Anantika; Sankhyan, Era (Asian Pacific Journal of Cancer Care, 2024)
Background: Metastatic urothelial carcinoma of the bladder is a rarely encountered condition at the time of diagnosis, with lymph nodes, bones, lungs, and liver being the common sites of metastasis. However, metastasis can also occur in uncommon locations. Case Presentation: This case report describes the unusual occurrence of metastasis in the perinephric region, renal fascia, and ovaries. It highlights the importance of distinguishing primary urothelial carcinoma of the ovary from metastatic lesions. Due to the lack of standardized treatment guidelines, management options should be tailored to each individual case. The prognosis of metastatic urothelial carcinoma remains unfavorable, with a limited life expectancy. Conclusion: This case report presents a case of metastatic urothelial carcinoma of the bladder with perinephric region and ovarian metastasis, detailing the course of treatment.